2016
DOI: 10.1007/s10646-016-1710-2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake route and resulting toxicity of silver nanoparticles in Eisenia fetida earthworm exposed through Standard OECD Tests

Abstract: Despite the increasing interest in silver nanoparticles toxicity still few works dealt with the hazards of nanosized Ag in soils (either dissolved in pore water or coupled to colloids) although disposal of biosolids in landfills has been reported as the major source of silver nanoparticles in terrestrial environments. Presently, Eisenia fetida was used to assess the toxicity of 5 nm sized PVP-PEI coated silver nanoparticles in soil through the implementation of different exposure media Standard Toxicity Tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…Antisari et al [ 223 ] reported for Co NP a reduction in soil microbial biomass and changes in its community composition, which may partly explain alterations in earthworms’ fatty acid composition. The uptake of TiO 2 NP via contaminated food seems to be of high relevance for terrestrial [ 224 , 225 ] and aquatic invertebrates [ 226 ]. This direct uptake pathway increases NP exposure and might influence the food quality through impacts on food-associated microorganisms.…”
Section: Np Effects In Communities and Consequences For Trophic Intermentioning
confidence: 99%
“…Antisari et al [ 223 ] reported for Co NP a reduction in soil microbial biomass and changes in its community composition, which may partly explain alterations in earthworms’ fatty acid composition. The uptake of TiO 2 NP via contaminated food seems to be of high relevance for terrestrial [ 224 , 225 ] and aquatic invertebrates [ 226 ]. This direct uptake pathway increases NP exposure and might influence the food quality through impacts on food-associated microorganisms.…”
Section: Np Effects In Communities and Consequences For Trophic Intermentioning
confidence: 99%
“…When combined with the dermal absorption of Ag + ions, this increased metabolism could explain the higher toxicity of AgNO 3 . However, (Diez-Ortiz et al, 2015b;Garcia-Velasco et al, 2016) showed that Ag is mainly internalized by soil ingestion. Our bioaccumulation results show that Ag can enter the earthworm body.…”
Section: Discussionmentioning
confidence: 99%
“…Inf 1). Four different Ag concentrations, C1, C2, C3 and C4, were used for the AgNP and AgNO 3 microcosms: 30 (± 20), 70 (± 10), 120 (± 15) and 280 (± 40) mg kg -1 (dry matter), respectively (these concentrations were chosen based on mortality rates reported in Garcia-Velasco et al (2016) and Gomes et al (2015)). Four different volumes of NM300K dispersant were used in the dispersant microcosms, which served as controls.…”
Section: Experimental Scheme (Earthworm Exposure)mentioning
confidence: 99%
“…Cells exposed to other nanoparticles, such as Ag NPs, nZVI NPs or ZnO NPs release significantly greater ROS amounts. Contrary to TiO 2 NPs, ROS production could be elicited by the metal ions released from these nanoparticles [11,29,30].…”
Section: Mrna Levels Of Detoxification Immune Antioxidant and Signal Transduction Moleculesmentioning
confidence: 99%